Bread Made from Wheat Flour and White Sesame Flour in Presences of Natural Improver - Ali, M.A.; Halim, M.A. (Pakistan Journal of Nutrition, 2013)
Addition of white sesame flour to wheat flour with different incorporation levels (5, 10.15%) in bread blend led to significant increase in nutritive value but with inferior quality with respect to crumb, crust color and bread volume. Proximate analysis of the wheat and white sesame flour were carried out. The rheological prosperities of the blends of wheat flour and white sesame flour were determined using a farinograph. To alleviate these inferior effects, natural improvers were used. Rheological test revealed, increase in water absorption value, dough development time and dough stability for all dough prepared from white sesame-wheat flour blend in presence of the two types of improvers. Characteristics of bread prepared from white sesame-wheat flour blend using the two improvers, revealed better result as for crumb color, crust color, aroma, texture and taste as compared to control bread, with a noticeable increase in bread volume.